How context influences the tactical-technical behavior of learners: the case of volleyball - Augusto Cézar Rodrigues Rocha; Auro Barreiros Freire; Alcilas Borges da Silva Junior; Leonardo Rodrigues Martins; Mariana Pereira Maia; Gustavo Palhares Mitre; Henrique de Oliveira Castro; Gustavo De Conti Teixeira Costa (Universidade Federal de Santa Catarina, 2020)
This study compared the tactical-technical behavior between two distinct situations of reduced volleyball games. The sample consisted of 12 games played by doubles, 6 of which were played in 3.0m x 3.0m (SIT1) and 6 of 2.0m x 4.5m (SIT2) courts. Thus, the behavior of 12 participants, with mean age of 16.7 ± 1.5 years and 3.2 ± 1.2 years of practice, was compared. The results showed that at reception, better results were obtained in adjustment and decision making in SIT2, whereas in SIT1, efficiency was higher; in setting, it was observed that SIT2 presented better results in technical performance, adjustment and efficiency, whereas in SIT1, efficiency was higher; in SIT2, attack, better results were observed in adjustment and decision-making. It was concluded that environmental restrictions influence the behaviors of learners, showing that different ecological contexts provide actions inherent to the specific game environment.